Cd2+ and Zn2+ Complexes with 2, 4, 6‐Tri(2‐pyridyl)‐s‐Triazine and Terephthalate for Rapid, High‐Capacity Adsorption of Congo Red. Issue 2 (1st February 2023) - Zhao, Yanfang; Zhao, Yongliang; Guo, Ziyang; Zhou, Dan; Yuan, Shuai; Zhang, Xueqiong; Chu, Haibin
Abstract: Three crystal complexes were designed and synthesised through the solvothermal method, with Cu 2+, Zn 2+, and Cd 2+ ions as the metal centres and 2, 4, 6‐tri(2‐pyridyl)‐ s ‐triazine (TPTZ) and terephthalate (BDC 2− ) as the ligands. Their compositions were determined to be Cd(TPTZ)Cl2 (Cd‐MOF), {[Zn(TPTZ)(BDC)] ⋅ 3H2 O}n (Zn‐MOF), and Cu2 (PCA)2 (BDC)(H2 O)2 (Cu‐MOF) (PCA − =2‐pyridinium amide), respectively. Cd‐MOF can adsorb 90 % of Congo red (CR) in 10 s at room temperature and atmospheric pressure, and CR removal was complete at 20 s over a wide pH range. The adsorption capacity for CR reached 1440 mg g −1 in 5 min. Selective adsorption was demonstrated in mixed dyes. The adsorption kinetic data agree well with the pseudo‐second‐order kinetic model. The Temkin model was successfully used to evaluate the adsorption isotherms of CR on Cd‐MOF at room temperature, suggesting that adsorption occurs through a hybrid of monolayer and multilayer mechanisms. Abstract : Three crystal complexes were designed and synthesised: Cd(TPTZ)Cl2 (Cd‐MOF), {[Zn(TPTZ)(BDC)] ⋅ 3H2 O}n (Zn‐MOF), and Cu2 (PCA)2 (BDC)(H2 O)2 (Cu‐MOF). Cd‐MOF could adsorb 348.3 mg g −1 of Congo red (CR) within 20 s over a wide pH range. Its adsorption capacity reached 1440 mg g −1 in 5 min, and it selectively adsorbed CR from mixed dyes. The adsorption of CR onto Cd‐MOF is based on a hybrid mechanism of monolayer and multilayer absorption.